Multi‐Component Crosslinked Hydrogel Electrolyte toward Dendrite‐Free Aqueous Zn Ion Batteries with High Temperature Adaptability. (27th January 2022) - Lu, Hongyu; Hu, Jisong; Wang, Litong; Li, Jianzhu; Ma, Xiang; Zhu, Zhicheng; Li, Heqi; Zhao, Yingjie; Li, Yujie; Zhao, Jingxin; Xu, Bingang
Abstract: Rechargeable aqueous Zn‐ion batteries (ZIBs) are always regarded as a promising energy storage device owing to their higher safety and durability. However, two problems have become the main trouble for the practical application of ZIBs such as the dendrite growth of Zn metal anode in electrolyte and the freezing of water solvent at low temperature. Herein, to overcome these challenges, a new strategy, multi‐component crosslinked hydrogel electrolyte, is proposed to inhibit Zn dendrites and realize low temperature environmental adaptability for ZIBs. Benefitting from the superior inhibition effect of the polyacrylamide and dimethyl sulfoxide (DMSO) on Zn dendrites, the coulombic efficiency of the symmetric cell of ≈99.5% is achieved during the Zn plating/stripping over 1 300 h, and the assembled full‐cell demonstrates the large specific capacity of 265.2 mAh g ‐1 and high cyclic stability with the capacity retention of 95.27% after 3 000 cycles. In addition, the full‐cell delivers stable operation at a wide temperature range, from 60 to −40 °C, due to the introduction of additive DMSO. This work provides an inspired strategy and novel opportunities to realize a dendrite‐free and wide‐temperature rechargeable aqueous Zn‐ion energy storage system. Abstract : An innovative multi‐component cross‐linked hydrogel electrolyte is designed for dendrite‐free aqueous Zn ion batteries with high‐temperature adaptability.